Viajes de vida, viajes de aula (2017)
This research proposal begins with an inquisitiveness of the subject who wants to research, from that being who removes and mobilizes him daily as a teacher, artist and subject in construction, assuming it from different pedagogical experiences that until today have allowed him to experience, emerging concepts from self-esteem, scream, rhizomes and self-portrait, which are used to observe: how do these conceptions intervene in every aspect of life and, at the same time, shapes the relationship of these with the learners? Therefore, this research gets to communicate about those experiences that become in practices and evolve because of the changes given from the art teachers’ posture, allowing the release, the recognition of him/herself, the connections and his/her acceptance, betting him on an own and others’ transformation.